Association of Serum Homocysteine Level with Acute Ischaemic Stroke among Young Adult Patients: Experience at a Largest Medical College Hospital in Bangladesh - Uddin, Mohammad Nur; Hakim, Maliha; Zannat, Tahira; Al Amin, Md; Dolan, Mohammad Abdur Rauf; Yusuf, Md Abdullah; Hasan, Mashfiqul; Islam, Muhammad Saiful; Ray, Swapon Kumar; Chowdhury, Md Faizul Islam (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: Hyperhomocysteinemia is emerging as a possible risk factor for stroke, possibly because of accelerated atherosclerosis. Objectives: This study was conducted to evaluate the association between the serum homocysteine level and ischemic stroke in young Bangladeshi patients. Methodology: This cross-sectional study was carried out among patients 18 to 40 years of either gender with sign and symptoms of acute focal neurological deficit, in the Department of Medicine of Dhaka Medical College Hospital, Dhaka, from January 2015 to December 2015. History taking and physical examination were done in a predesigned data collection sheet. Then required investigations like CT-scan of brain, fasting serum homocysteine, fasting blood sugar, 2 hours ABF blood glucose, HbA1c and fasting lipid profile were done. Results: Out of 96 patients after completing brain imaging 61(65.0%) patients were found suffering from ischemic stroke. Among the patients 74 had normal homocysteine level, 17 patients had moderate hyperhomocysteinemia and 5 patients had intermediate hyperhomocysteinemia. Mean levels of fasting serum homocysteine were significantly higher in patients those had ischemic stroke (16.02 μmol/L, 95% CI: 12.87 to 19.87) compared with those who did not have ischemic stroke (10.47 μmol/L, 95% CI: 9.16 to 11.95, P<0.001). Logistic regression showed fasting homocysteine as an important independent risk factor, with an adjusted OR of 1.1 (95% CI: 1.1 to 1.2; p=0.04966) for every 1 μmol/L increase in homocysteine. Conclusion: The relationship between increasing homocysteine and ischemic stroke risk is strong, graded, and significant. Journal of National Institute of Neurosciences Bangladesh, January 2023;9(1):24-29